2013
DOI: 10.1556/achrom.25.2013.3.7
|View full text |Cite
|
Sign up to set email alerts
|

Ion-pair RP-HPLC method for the estimation of eberconazole nitrate in bulk form and in pharmaceutical dosage forms

Abstract: Summary. An isocratic ion-pair reversed phase high-performance liquid chromatography-ultraviolet (RP-HPLC-UV) method for analysis of eberconazole nitrate in bulk and in pharmaceutical dosage forms has been developed and validated. Best separation was achieved on Lichrospher C18 column (250 mm × 4.6 mm, 5 μm) using a mobile phase of 10 mM potassium dihydrogen phosphate containing 10 mM tetra-butyl ammonium hydroxide (pH adjusted to 2.8 with ortho phosphoric acid) and methanol (75:25, v/v) at a flow rate of 1.0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Eberconazole Nitrate was estimated in bulk form and pharmaceutical dosage forms by M. Vamsi Krishna using Ion-Pair RP-HPLC Method. 75% of 10 mM potassium dihydrogen phosphate containing 10 mM tetra-butyl ammonium hydroxide (cationic IPR) and 25% of methanol were used as a mobile phase [ 15 ]. A high pH ion-pairing strategy was used in 2015 by J. R. Dentona for the chromatographic determination of 2-hydroxypyridine-1-oxide (HOPO) in pharmaceutically relevant materials using hydroxy benzotriazole (HOBt) as a coupling reagent (cationic IPR) [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Eberconazole Nitrate was estimated in bulk form and pharmaceutical dosage forms by M. Vamsi Krishna using Ion-Pair RP-HPLC Method. 75% of 10 mM potassium dihydrogen phosphate containing 10 mM tetra-butyl ammonium hydroxide (cationic IPR) and 25% of methanol were used as a mobile phase [ 15 ]. A high pH ion-pairing strategy was used in 2015 by J. R. Dentona for the chromatographic determination of 2-hydroxypyridine-1-oxide (HOPO) in pharmaceutically relevant materials using hydroxy benzotriazole (HOBt) as a coupling reagent (cationic IPR) [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…A detailed literature survey for methylparaben, mometasone furoate and eberconazole nitrate revealed that determination of individual compound or combination with other drugs have been reported by HPLC [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] , LCMS [17][18] , electrophoresis 19 and spectrophotometric method 20 .…”
mentioning
confidence: 99%